Rational Way of Forming Stubble Coulisses under North Kazakhstan Conditions - V. L. Astaf'ev (Сельскохозяйственные машины и технологии)
The main limiting factor for increasing yields in the arid steppe conditions of Northern Kazakhstan is moisture. Shoots are usually uneven due to the lack of moisture at the initial stage of their growing. The main source of moisture in this period is winter precipitation. Currently, the following methods of winter precipitation moisture accumulation are used in North Kazakhstan: leaving high standing stubble, seeding coulisses on pure fallow fields, herbicide (chemical) fallow field, snow ridging, harvesting of crops with continuous combining; and forming stubble coulisses. The most preferable way of increasing snow moisture accumulation is the formation of stubble coulisses that can be done in two ways.Research purpose Efficiency evaluation of the ways of forming stubble coulisses.Materials and methods Agroengineering and technological evaluation is used as a main research method of different ways of forming stubble coulisses, which is followed by the selection of a more preferable way.Results and discussion It has been found that in snowy winter both ways of forming stubble coulisses – with alternative passes of a direct combining reaper and a stripping reaper and using a direct combining reaper with a stripper adapter – have shown the same results. However, when there is a little snow in winter, the second way provides more intensive snow accumulation.Conclusions It has been experimentally found that using the direct combining reaper with the stripper adapter decreases labour inputs by 17.8% and total costs by 23.8% as compared to the formation of coulisses by using sequential passes of the direct combining and the stripping reapers. It has been found that the formation of stubble coulisses every 5-9 meters along with in-line para-plowing at a depth of up to 35 cm provides the highest yield increase of in snowy winter as compared to the conventional ways of moisture accumulation.